2002
DOI: 10.1001/archinte.162.17.1985
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Survival Among US Whites and Minorities

Abstract: Survival rates in patients with cancer have improved in recent years, but racial or ethnic differences in survival rates and in RRs of cancer death persist. Additional studies are needed to clarify the socioeconomic, medical, biological, cultural, and other determinants of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
122
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 473 publications
(135 citation statements)
references
References 42 publications
7
122
1
Order By: Relevance
“…Although there are few studies that have evaluated the influence of Hispanic ethnicity on lung cancer survival, [1][2][3]59 our study is consistent with these investigations. However, some studies have found mixed results regarding the influence of nativity status on survival from NSCLC.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although there are few studies that have evaluated the influence of Hispanic ethnicity on lung cancer survival, [1][2][3]59 our study is consistent with these investigations. However, some studies have found mixed results regarding the influence of nativity status on survival from NSCLC.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have demonstrated that Hispanics have 50% lower lung cancer mortality rates than non-Hispanic whites (NHWs) [1][2][3][4][5] ; however, Hispanics are more likely to be diagnosed at advanced stages [1][2][3][4]6 and less likely to receive treatment. 7,8 Relatively lower cancer mortality among US Hispanics is consistent with the so-called Hispanic paradox, referring to better health relative to NHWs despite disadvantages in socioeconomic status (SES).…”
Section: Introductionmentioning
confidence: 99%
“…The place of estrogen receptor modifiers (SERMs) in the treatment of breast cancer is now well established. Survival in breast cancer patients in the developed world has increased considerably over the past several decades, due principally to more widespread screening and the systematic use of adjuvant therapy [8,9] . Whilst adjuvant therapy with SERMs, aromatase inhibitors, cytotoxic agents, monoclonal antibodies and other agents has transformed the outlook for breast cancer patients, there remains considerable unmet need for improvements in both efficacy and tolerability.…”
Section: Topic Highlightmentioning
confidence: 99%
“…Critical data from the Surveillance, Epidemiology, and End Results (SEER) program (1992-2000) show that the incidence of gallbladder cancer (GBC) is assessed at 2.5 per 100,000 persons making it the most common primary biliary tract malignancy, representing 46% of all such malignancies [1]. Major pockets of significantly high occurrences include Central and South America (Chile, Mexico, and Bolivia), Central and Eastern Europe (Hungary, Poland, Czechoslovakia, and Austria) and Japan [2].…”
Section: Introductionmentioning
confidence: 99%